2017
DOI: 10.1111/1911-3846.12344
|View full text |Cite
|
Sign up to set email alerts
|

Public Company Audits and City‐Specific Labor Characteristics

Abstract: Prior research emphasizes the centrality of audit offices in understanding auditing practices, and documents significant interoffice variation in audit outcomes based on industry expertise and office size. Our study examines how two city‐specific labor characteristics also affect audit offices and local audit markets: the city's average educational attainment, and the number of accountants in a city, which proxy for a city's human capital. Our argument draws on the urban economics literature and predicts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…25. While Dee et al (2015) do not find this to be a significant characteristic in their subset of firms that disclose component auditor use, recent studies find local education levels and professional certifications of relevant individuals to be informative characteristics (e.g., Beck et al 2018;Hoitash et al 2016;Ge et al 2011;Prawitt et al 2009). Nagy et al (2020) find that the number of CPAs in U.S. audit firm offices is positively associated with audit quality, measured by the likelihood of restatements and discretionary accruals.…”
Section: Research Design Sample Selectionmentioning
confidence: 99%
“…25. While Dee et al (2015) do not find this to be a significant characteristic in their subset of firms that disclose component auditor use, recent studies find local education levels and professional certifications of relevant individuals to be informative characteristics (e.g., Beck et al 2018;Hoitash et al 2016;Ge et al 2011;Prawitt et al 2009). Nagy et al (2020) find that the number of CPAs in U.S. audit firm offices is positively associated with audit quality, measured by the likelihood of restatements and discretionary accruals.…”
Section: Research Design Sample Selectionmentioning
confidence: 99%
“…Chung, Cho, Lee, and Son (2017) found that firms with a strong labor union tend to choose high-quality auditors. Beck, Francis, and Gunn (2018) argued that human capital is associated with the supply of audit and found that US firms headquartered in cities with high average educational levels are more likely to choose a non-Big 4 auditor. The migration of wealthy elites is increasingly publicized in China.…”
Section: Other Institutional Factors and Auditor Choicementioning
confidence: 99%
“…Examples of characteristics corresponding to improved quality include auditor size (DeAngelo ), office size (Francis et al ; Francis and Yu ), or industry expertise (Balsam et al ; Krishnan ; Reichelt and Wang ). More recently, Beck et al () documented a positive association between audit quality and the average education level in the MSA of the engagement office, and Hoopes et al () linked auditor salaries to audit quality.…”
Section: Prior Literature and Motivationmentioning
confidence: 99%